Special needs: the vegetarian athlete - Cox, G. (2000)
This chapter describes various categories of vegetarian diets and discusses the impact of vegetarian eating on meeting current dietary goals and guidelines for optimal sports performance. Studies investigating the benefit of consuming a vegetarian diet on sports performance are reviewed. Potential nutritional concerns of different categories of vegetarian diets in an athletic population are also discussed. Practical guidelines for health professionals to ensure appropriate nutritional strategies are used to assist vegetarian athletes in meeting daily nutritional requirements are outlined. SUMMARY: As dietary surveys of vegetarian athletes are scarce, this chapter has reported nutrient intakes of non-athletic adult populations ollowing lact-ovo-vegetarian and vegan diets. Many of these dietary survey studies have focussed on elderly female populations, hardly representative of athletes. Further dietary survey studies on athletic populations are required to fully understand the influence of a long-term vegetarian diet on exercise performance. Minimal information is available on the nutrient adequacy of restrictive vegetarian diets such as fruitarian and macrobiotic diets, particularly among athletic populations. The high-CHO content usually consumed in vegetarian diets is conducive to restoring and maintaining adequate glycogen stores in athletes in hard training programs. A well-planned lacto-ovovegetarian diet and vegan diet will meet the nutrient requirements of most athletes. However, meeting energy requirements of athletes with high energy expenditures may be difficult. Although animal foods are good sources of protein, iron, zinc and vitamin B12, and dairy products are rich sources of calcium, alternative sources are available in most vegetarian diets. Energy-dense plant foods high in protein should be encouraged for athletes with high energy and protein requirements. Food sources fortified with vitamin B12 should be included in a vegan diet to ensure adequate amounts are consumed. Further res earch is required to gain a better understanding of the influence of a long-term vegetarian diet on menstrual status in female athletes. Athletes following a `fussy meat-eating diet` appear to face similar nutrient concerns to vegetarians and may be at greater risk of nutritional inadequacies as they often fail to replace red meat with suitable alternatives.